THE URGENCY OF INDONESIA IN RATIFYING THE CONVENTION RELATING TO THE STATUS OF 1951 REFUGEES AND 1967 NEW YORK PROTOCOL TO DETERMINE THE STATUS OF REFUGEES IN INDONESIA - Firdausi, Yoga (jfpublisher, 2022)
Refugee is one of the problems that needs more attention, especially for the hosted country which has ratified The Convention Relating to The Status of 1951 Refugees and 1967 New York Protocol or countries that have not ratified it. However, it should be remembered that based on the principle of non- refoulement, a country may not expel or return asylum seekers until they get status as refugees who must be protected by the receiving country. The purpose of this paper is to provide an analysis and description of the issue of granting refugee status in Indonesia considering that Indonesia still needs to unify and ratify the Convention Relating to the Status of 1951 Refugees and 1967 New York Protocol. The research method used in examining the problem is legal comparison with functional methods and micro approaches (Source of Norms). The benefits of Indonesia ratifying the Convention Relating to the Status of the 1951 Refugees and the 1967 New York Protocol the determination of refugee status will be fully transferred to Indonesia's rights without depends on the United Nations High Commissioner for Refugees (UNHCR) as a United Nations main aspect that specifically deal with refugees.